2015
DOI: 10.1002/acr.22488
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Isometric Thigh Muscle Strength and Minimum Clinically Important Differences in Knee Function in Osteoarthritis: Data From the Osteoarthritis Initiative

Abstract: Objective To determine the relationship between thigh muscle strength and clinically relevant differences in self-assessed lower limb function. Methods Isometric knee extensor and flexor strength of 4553 Osteoarthritis Initiative participants (2651 women/1902 men) was related to Western Ontario McMasters Universities (WOMAC) physical function scores by linear regression. Further, groups of Male and female participant strata with minimal clinically important differences (MCIDs) in WOMAC function scores (6/68)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 45 publications
6
54
3
Order By: Relevance
“…In the first study, the relationship between thigh muscle strength and clinically relevant differences in self-assessed lower limb function was estimated, while in the second investigation testretest reliability of lower limb isokinetic endurance in COPD patients was taken in examination. Averagely, both studies described a threshold of about 6% 29 and 10% 30 respectively to determine a minimally clinical relevant change. It has to be considered that our data reflected a performance in a healthy population; however, the magnitude of error in the system showed a range concretely inferior to the minimal clinically relevant differences detected in these investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study, the relationship between thigh muscle strength and clinically relevant differences in self-assessed lower limb function was estimated, while in the second investigation testretest reliability of lower limb isokinetic endurance in COPD patients was taken in examination. Averagely, both studies described a threshold of about 6% 29 and 10% 30 respectively to determine a minimally clinical relevant change. It has to be considered that our data reflected a performance in a healthy population; however, the magnitude of error in the system showed a range concretely inferior to the minimal clinically relevant differences detected in these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical standpoint, as comparison with our data, we extract data from Ruhdorfer et al 29 and Ribeiro et al 30 . In the first study, the relationship between thigh muscle strength and clinically relevant differences in self-assessed lower limb function was estimated, while in the second investigation testretest reliability of lower limb isokinetic endurance in COPD patients was taken in examination.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in consistence with our study, several studies so far have demonstrated the correlation between quadriceps strength and functionality. 19,20 The results of these studies indicated that decreased isometric quadriceps muscle strength is related to knee symptoms and WOMAC functional disability. 19,20 25-hydroxy vitamin D levels were not correlated with quadriceps muscle strength and patients' functional status in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…19,20 The results of these studies indicated that decreased isometric quadriceps muscle strength is related to knee symptoms and WOMAC functional disability. 19,20 25-hydroxy vitamin D levels were not correlated with quadriceps muscle strength and patients' functional status in the current study. Similarly, Al-Jarallah et al 21 did not find any relationship between 25-(OH)D and the functional status of patients with primary knee OA in their crosssectional study.…”
Section: Discussionmentioning
confidence: 93%
“…The MID is a useful expression defined as “the minimal amount of change required between two points in time to be confident that a patient has truly changed” 23. A reduction of 4% in isometric force has been suggested as the minimal change to bring about a relevant difference in osteoarthritis of the knee 24. Similarly, a preliminary result by Quessada et al suggested an MID of 33 Nm for QMVC in individuals with COPD undergoing exercise training 25.…”
Section: Introductionmentioning
confidence: 99%